1962
DOI: 10.1099/00221287-29-1-127
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Sporidesmin and Sporidesmolides by Wild Isolates of Pithomyces chartarum in Surface and in Submerged Culture

Abstract: SUMMARYFour wild and two laboratory isolates of Pithomyces chartarum were grown under identical conditions, in submerged and in surface culture ; yields of organisms and utilization of medium constituents are reported. Sporidesmin was produced in submerged culture and in surface culture by all the isolates examined but these showed differences of up to a t least 100-fold in ability to produce the metabolite. Sporidesmolides were not isolated from cultures which did not sporulate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1967
1967
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…The same isolate, grown in submerged liquid culture, formed abundant vegetative mycelium but no spores, and only traces of angolide were isolated from such cultures. Similar results have been recorded for sporidesmolide production by P. chartarum (Dingley et al 1962). This evidence, taken with the previous failure to obtain more than traces of depsipeptide from feebly sporing liquid surface cultures of P. sacchari 1~1102686 (Bishop et al 1965), established that the angolide from P. sacchari is associated with the spores.…”
Section: Morphological Location Of Angolide In Pithomyces Saccharisupporting
confidence: 73%
“…The same isolate, grown in submerged liquid culture, formed abundant vegetative mycelium but no spores, and only traces of angolide were isolated from such cultures. Similar results have been recorded for sporidesmolide production by P. chartarum (Dingley et al 1962). This evidence, taken with the previous failure to obtain more than traces of depsipeptide from feebly sporing liquid surface cultures of P. sacchari 1~1102686 (Bishop et al 1965), established that the angolide from P. sacchari is associated with the spores.…”
Section: Morphological Location Of Angolide In Pithomyces Saccharisupporting
confidence: 73%
“…Measurement of grass minimum temperatures gives some indication of heat input into the base of pasture, but the length of time for which humidity is 100% is affected not only by rainfall but also by day length (perhaps the reason for the low spore counts of the first danger periods in December and January), cloud cover, soil moisture and wind amongst other factors. it was considered that with sporidesmin being produced with P. chartarum spores in amounts proportional to their numbers (done et al 1961 ;dingley et al 1962;davison & Marbrook 1965), counts of spores in pasture herbage would give a more direct measure of sporidesmin content than measurement of the physical conditions governing their production (di Menna & Bailey 1973). depending on the weather, populations of aging spores may have lost toxicity because sporidesmin is leached from them by rain and destroyed by sunlight (Marbrook & Matthews 1962;Clare & Gumbley 1962;Clare & Mortimer 1964), but these would be present only at the end of danger periods.…”
Section: Spore Counts In Pasturementioning
confidence: 99%
“…There was no evidence that strains of similar toxicity occurred together in one place at one time. Dingley et al (1962) and Davison & Marbrook (1965) measured sporidesmin production by a number of strains of Pithomyces chartarum. Because there were differences in the media, incubation times and temperatures, and in the methods of sporidesmin assay used by each group, including the present authors, the absolute values for sporidesmin production are not comparable and the relative toxities of strains used by different workers cannot be determined.…”
Section: E D I Menna J C a M P B E L L A N D P H Mortimermentioning
confidence: 99%
“…Ross & Thornton (1962) and Ross (1962), using several strains, found that different isolates grown under similar conditions varied in the amount of sporidesmin they produced and that there was a general relationship between spore numbers and sporidesmin production. Dingley, Done, Taylor & Russell (1962) using six strains, some of which did not spore freely, found more than hundredfold differences in amounts of sporidesmin produced under standard conditions. Davison & Marbrook (1969, using ten strains which spored well in culture, found only sevenfold differences.…”
Section: Introductionmentioning
confidence: 98%